Evaluación agronómica y rendimiento de grano de seis nuevos maíces híbridos ‘30f87’, ‘3041’, ‘30k73’, ‘30k75’, ‘30f35’ y ‘3031’ en condiciones de riego. - Duche Mariño, José Luis (2011)
On land belonging to Mr. Joseph Duche Zurita, located at Km 1.5 of the way Montalvo - Babahoyo, Campus 'La Guadalupe', Canton Montalvo, Los Rios Province, is a test used eight corn hybrids tested, with the aim of evaluate the agronomic performance of six new corn hybrids '30F87 ', '3041', '30K73 '; '30K75'; '30F35 'and '3031', along with the witnesses 'Iniap H - 601' and 'Agroceres AG - 003' under irrigated conditions, identify or hybrids yield performance and grain capacity per unit area per unit time and to analyze the grain yield economically according to the cost of treatments. Experimental design was used "randomized block" in four replications. The experimental plot was composed of 4 rows of 6 m in length, spaced at 0.80m, giving an area of 19.2m2. The separation between plants in each row was 0.20m, giving a population of 62,500 plants per hectare. Variables were evaluated: male and female flowering, height of insertion of ear and plant, leaf area index, pods per plant, diameter and length of ears, rows of kernels per ear, kernels per ear; relationship grain - corn husk, weight of 100 grains and grain yield. We performed the analysis of variance of each variable, and to determine the statistical difference between the means of the hybrid test was used Tukey statistical significance at 95% probability.